2023
DOI: 10.1021/acsagscitech.3c00074
|View full text |Cite
|
Sign up to set email alerts
|

Plant Viral Nanocarrier Soil Mobility as a Function of Soil Type and Nanoparticle Properties

Abstract: The use of nanoparticles for agrochemical delivery is an important step toward achieving global food security. Specifically, the ability to target the delivery of pesticides and other useful chemicals into the soil will greatly improve the efficiency and efficacy of these molecules, mitigating crop losses associated with pests and parasitic organisms. While synthetic nanoparticles can be a good delivery vehicle and demonstrate high mobility in the soil, their fate and persistence have some implications for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Tannins and β-glucan are also being studied as potential nanocarriers for AIs [ 139 ]. It has been reported that the tobacco mild green mosaic virus (TMGMV) and other plant viruses can act as nanocarriers for AIs to effectively deliver pesticides to target cells [ 140 , 141 ]. NPCs utilizing nanocarriers possess certain advantages; however, concerns and challenges persist regarding their application.…”
Section: Nano-agrochemicals (Nacs)mentioning
confidence: 99%
“…Tannins and β-glucan are also being studied as potential nanocarriers for AIs [ 139 ]. It has been reported that the tobacco mild green mosaic virus (TMGMV) and other plant viruses can act as nanocarriers for AIs to effectively deliver pesticides to target cells [ 140 , 141 ]. NPCs utilizing nanocarriers possess certain advantages; however, concerns and challenges persist regarding their application.…”
Section: Nano-agrochemicals (Nacs)mentioning
confidence: 99%
“…A very recent paper by Ristroph et al on novel scalable nanocarrier formulations for pesticides has quickly received a large number of views. Examples of other papers on nanomaterials relevant for pesticide formulations are as follows: sustainable nanomaterial approaches to essential oil delivery for disease prevention in soy; pesticide formulation processes using polymeric nanoparticles; metal–organic frameworks for controlled release insecticide formulations; utilizing plant virus nanoparticles as delivery vehicles in soil; and bacteria-based nanobiopesticides for plant disease management . Other examples of novel applications that have been published this year are smart gene delivery systems for plants using amine-functionalized carbon dots, nitrogen-doped carbon dots to address drought stress in maize, and nanoparticles doped with micronutrients and P to reduce nutrient leaching to groundwater .…”
mentioning
confidence: 99%